Electrical properties of Ba doped LSGM for electrolyte material of solid oxide fuel cells - Raghvendra; Singh R.K.; Singh P. (My University, 2025)
We report our investigations on Lanthanum Strontium Magnesium Gallate, LSGM, La0.8Sr0.2Ga0.8Mg0.2O 3-δ doped with Barium at Strontium site having composition La0.8(Sr0.1Ba0.1)Ga0.8Mg 0.2O3-δ (LSBGM). The pure cubic phase along with some additional phase was confirmed by XRD pattern. Electrical properties of the Composition LSBGM [La0.8(Sr0.1Ba0.1)Ga 0.8Mg0.2O3-δ] prepared by solid state route, was studied employing impedance spectroscopy in the temperature range 573 K-993 K and frequency range 20 Hz-1MHz. The total ionic conductivity of the composition was found to be 0.072 S.cm-1 at 953 K and the activation energy from Arrhenius plot was found to be 1.16 eV in the measured temperature range. This confirms oxygen ion conductivity in the system. SEM micrograph shows the uniform densed particle morphology with gains of average size 200 nm. © 2013 American Institute of Physics.